Formulation and anti-bacterial of liquid soap combination of Citronella (Cymbopogon nardus L. Rendle), Cinnamon (Cinnamomum burmanni Ness Ex Bi.), and Orange Lemon (Citrus lemon L.) Essential Oils on Staphylococcus epidermidis - Nafisah, Umi; Suhesti, Iin; Albetia, Puput (Media Farmasi: Jurnal Ilmu Farmasi, 2022)
The condition of our community in the midst of a pandemic makes us aware of the importance of cleanliness. One way to maintain cleanliness is to clean our self with soap. Cinnamon has antibacterial activity against Staphylococcus aureus and Staphylococcus epidermidis. Lemongrass has antibacterial activity against Staphylococcus aureus, while lemons are able to inhibit the growth of Staphylococcus epidermidis and Propionibacterium acnes bacteria. The aims of this study are to determine the formulation and physical stability of liquid soap with a combination of lemongrass, cinnamon, and lemon essential oils and to determine its antibacterial activity against Staphylococcus epidermidis. Physical evaluation of soap includes organoleptic, homogeneity, viscosity, pH, and specific gravity which is compared with SNI, and hedonic test is performed. Antibacterial test was performed against Staphylococcus epidermidis.The results of the study obtained homogeneous liquid soap preparations, thick liquid form, a yellow-orange color, distinctive smell of citronella. Specific gravity (g/ml) test results meet the requirements of SNI, which is between 1.01 – 1.10 at room temperature. The results of the pH test meet the requirements of SNI, which are between 8 – 11. The results of the viscosity (cPas) test show that there is an increase in viscosity from week 1 to week 6. The increase in viscosity is related to particle size during storage. The foam height (cm) test results obtained F1: 11.76 ± 0.67, F2: 11.67 ± 1.25, F3: 11.33 ± 1.02, F4: 11.60 ± 0.79, F5: 11.18 ± 0.84. The results of the hedonic test obtained that the average respondent liked the foam produced, the shape, color, comfort when used, and the smell. The lowest value of the hedonic test is the smell of the liquid soap that is produced. From the results of antibacterial test against S. Epidermidis, it is known that liquid soap has antibacterial activity with strong inhibitory power.